Penerapan pembelajaran berbasis diferensiasi dalam materi ekosistem untuk siswa kelas v mi fathul huda pucung lor - Nada, Siti Akmalia (Maliki Interdisciplinary Journal, 2025)
Modern education demands innovative approaches that accommodate the diverse learning needs of students. Differentiated instruction is an effective method to enhance students' understanding of subjects, including ecosystem learning. This study aims to analyze the implementation of differentiated instruction in teaching ecosystems to fifth-grade students at MI Fathul Huda Pucung Lor and its impact on student engagement and comprehension. The differentiation strategy was applied in three key aspects: content, process, and product. The results indicate that this approach successfully increased students' learning motivation, critical thinking skills, and understanding of ecosystem concepts. Additionally, differentiated instruction fostered the development of social skills through collaboration and group discussions. Thus, this approach can serve as an effective model for improving the quality of education, particularly in science learning at the elementary school level.